2012
DOI: 10.1016/j.ijscr.2012.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Subtle mesenteric avulsion in a traumatic abdominal wall hernia: A case report

Abstract: Mesenteric avulsion in TAWH is rare and difficult to diagnose and a high index of suspicion is warranted despite normal findings on initial assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A previous systematic review presented 20 cases of mesenteric avulsion following blunt abdominal trauma and found only 25% of cases presenting with shock and/or haemodynamic instability. Previous studies have also suggested that up to 58% of mesenteric avulsion injuries could be missed during the initial clinical assessment and imaging [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review presented 20 cases of mesenteric avulsion following blunt abdominal trauma and found only 25% of cases presenting with shock and/or haemodynamic instability. Previous studies have also suggested that up to 58% of mesenteric avulsion injuries could be missed during the initial clinical assessment and imaging [ 9 ].…”
Section: Introductionmentioning
confidence: 99%